Performance Evaluation of Carbon‐Based Printed Perovskite Solar Cells under Low‐Light Intensity Conditions. Issue 10 (9th July 2022) - Kim, Cuc Mai Thi; Perera, Malalgodage Amila Nilantha; Katz, Marcos; Martineau, David; Hashmi, Syed Ghufran
Abstract : The use of photovoltaics (PVs) to harvest energy inside modern building environments has great potential for energizing a wide range of futuristic self‐powered electronic devices, Internet of Things (IoT), and sensors using available ambient light. Among the various PV technologies, hole‐conductor‐free carbon‐based printable perovskite solar cells (CPSCs) have attracted significant interest, owing to their impressive PV performance under standard full sunlight conditions, robust stability, and printable fabrication methods. Nevertheless, their ability to harvest indoor light has been rarely explored. Here we report PV performance characterization of these printable CPSCs, and a systematic comparison of their PV performance under commonly available fluorescent (FL) and light‐emitting diode (LED)‐based lamps at various low lux light intensities that replicate standard indoor environmental conditions. To consolidate the proven stability of these CPSCs, the results of one stability test standardized as ISOS‐D‐1, which supports the motivation of their possible deployment under mild indoor lighting conditions are presented. The effective functioning of these CPSCs is also demonstrated for energizing an electrical node as evidence of their potential to be used as an alternative light‐harvesting solution for the targeted futuristic IoT‐based ecosystem. These results greatly support the goal of developing all printed and sustainable IoT devices with robust performance stability. Abstract : Systematic photovoltaic characterization of carbon‐based printable solar cells (C‐PSCs) is accounted for in this work along with a successful demonstration of the functioning of a temperature sensing node that was energized with an array of these printable solar cells.